Diversity of wood-inhabiting fungi (Basidiomycota) in Мacedonian cultural heritage - Kovachovska, Liljana; Rusevska, Katerina; Karadelev, Mitko (Macedonian Journal of Ecology and Environment, 2020)
The study of biological damage of cultural monuments in the Republic of North Macedonia was conducted between 2012 and 2016. The research was focused on the biodeterioration caused by wood-inhabiting fungi and slime moulds. Eighty-four cultural monuments in total, including monasteries, churches, and many old houses were inspected in different parts of the country. A total number of 109 wood-inhabiting fungi were observed both on the indoor wood construction (ceiling, stairs, inner portions of the roof, etc.) and external woodwork (gateway, bridge, outer door, roof, stairs, etc.). In this paper are presented the fungi from the phylum Basidiomycota. The majority of the identified species belong mainly to the genera: Antrodia, Athelia, Botryobasidium, Ceriporiopsis, Coniophora, Dacrymyces, Gloeophyllum, Hyphoderma, Hyphodontia, Phanerochaete, Peniophora, Phlebia, Postia, Stereum, Tapinella, Tomentellina etc. Decay fungi prevailed on the roof constructions of the inspected buildings. Fresh fungal damage found in monasteries and churches is detrimental to wood constructions and frescoes, and it must be eliminated in order to preserve important cultural heritage.